RCEP: The Opportunity for Indonesia and Steps of Its Implementation, An Insider's Perspective - Donna Gultom (Center for Indonesian Policy Studies (CIPS), 2020)
Amid the Covid-19 pandemic that weakens the global economy, 15 countries have finally signed the Comprehensive Regional Economic Pact (RCEP), which officially establishes it as the world's largest trade pact. The signing of the RCEP is believed to be the commitment of its members to restore the world economy and reignite global trade spirit. For Indonesia, RCEP has a great potential in opening up new markets and easing the entry of Foreign Direct Investment, especially in industries that develop e-commerce and industrial revolution 4.0. Hence, the government needs to prioritize structural and policy adjustments to increase national competitiveness and boost foreign and domestic investment. CIPS Senior Fellow, who is also the RCEP negotiation leader, Donna Gultom, shares her perspective and future policy steps for Indonesia to maximize this agreement's benefit in the latest CIPS policy summary.
Keywords: 330; RCEP; ASEAN; FDI; Foregign Direct Investment; Donna Gultom; international trade; China